Influence of brand differential on motivation to conform and manufacturer versus store brand purchase intention - Ellie Tran; Ayse N. Balas; Chris Y. Shao; Alan J. Dubinsky; Larry Jackson (International Journal of Business Science & Applied Management (IJBSAM), 2014)
Relationships and characteristics that influence consumers' purchase decision between store brand and manufacturer brand product offerings have emerged as an interesting and practical area of research. From a management perspective, understanding the process by which consumers make purchase choices between these brand offerings would lead to both theoretical and practical applications. Therefore, this study attempts to enhance understanding about the factors that influence consumers' manufacturer versus store brand purchase decisions. A conceptual model is developed to integrate the manner by which a consumer's motivation to conform to the perceived social norm of purchasing manufacturer brand products influences this purchase decision. The model is tested using survey data. Findings indicate the importance of the intensity of perceived differences between store brand and manufacturer brand product offerings in affecting consumers' purchase intention of these products. The relationship is also mediated by consumers' motivation to conform to manufacturer brand products in their purchase decision.
Keywords: 650; manufacturer brand; store brand; brand differential; motivation to conform